2020
DOI: 10.1016/j.media.2020.101699
|View full text |Cite
|
Sign up to set email alerts
|

Surgical spectral imaging

Abstract: Highlights Wider sensor availability and miniaturisation are pushing speed/resolution limits. Small surgical datasets exist in many specialities but no standard format. Data-driven analysis avoids modelling, improves speed, addresses uncertainty. RGB-based functional imaging could exploit existing cameras, chip-on-tip devices. Clinical validation with standardised devices and data needed for translation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
114
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(116 citation statements)
references
References 181 publications
(224 reference statements)
0
114
0
2
Order By: Relevance
“…Finally, this short and succinct review has focused on research directions that are in active development. Due to limitations of space, we have not discussed opportunities around using computer vision with different imaging systems or spectral imaging despite the opportunities in AI systems to resolve ill posed inverse problems in that domain [58]. Additionally, we have not covered in detail work in vision for the entire OR but this is a very active area of development with exciting potential for a wider team workflow understanding [3].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, this short and succinct review has focused on research directions that are in active development. Due to limitations of space, we have not discussed opportunities around using computer vision with different imaging systems or spectral imaging despite the opportunities in AI systems to resolve ill posed inverse problems in that domain [58]. Additionally, we have not covered in detail work in vision for the entire OR but this is a very active area of development with exciting potential for a wider team workflow understanding [3].…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative hyperspectral imaging, artificial intelligence, deep machine learning, augmented reality, fusion of preoperative CT- or MRI-scans to IOUS and the operation field, and other technical developments will be possible in the near future using the robotic system, enabling new perspectives in hepato-biliary surgery and hopefully achieving better oncological results and patient survival [ 1 , 4 , 8 , 22 , 32 , 36 , 37 , 38 , 39 , 40 ]. Until then, ICG staining may serve as an additional helpful intraoperative aid in patients undergoing robot-assisted, atypical liver resection, providing real-time images and helping to plan intraoperatively and perform surgery in an individual, tissue-sparing way.…”
Section: Discussionmentioning
confidence: 99%
“…(iv) The valuable wavelengths for the identification of tumors could be selected from NIR-HSI data using resected specimens. In this study, OTN-NIR MSI was investigated using commercially available filters via straightforward construction; however, spectral images with high wavelength resolution could be obtained by adopting an acoustic tunable filter (AOTF) and a liquid crystal tunable filter to select the wavelength before imaging or light output [21,29,30]. In particular, a combination of an AOTF and a supercontinuum light source is promising because high power output and fast wavelength switching can be obtained.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicate that multispectral imaging (MSI) using selected wavelengths in the range of OTN-NIR could potentially recognize invisible cancer and organs during surgery without labeling with a fluorescent probe. However, to date, only studies on laparoscopic HSI or MSI using less than 1000 nm light have been reported [19][20][21].…”
Section: Introductionmentioning
confidence: 99%